2015
DOI: 10.1007/s00253-015-6943-0
|View full text |Cite
|
Sign up to set email alerts
|

A small-molecule norspermidine and norspermidine-hosting polyelectrolyte coatings inhibit biofilm formation by multi-species wastewater culture

Abstract: Norspermidine is a potent and non-bactericidal small-molecule inhibitor of biofilm growth. In this study, impacts of norspermidine on biofilm control and existing biofilm dispersal by a mixed culture from wastewater treatment systems were investigated. A surface-mediated releasing approach for prevention of bacterial biofilm formation was established via encapsulating norspermidine into polyelectrolyte multilayer coatings. Results showed that the presence of norspermidine (500-1000 μM) in medium remarkably pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…Yet another possible target could be the phytochemicals compounds able to enhance dispersal of biofilms mainly by targeting the breakdown of the extracellular polysaccharide that makes up the extracellular matrix. Some compounds like norspermidine have been reported to have an enhanced dispersal of multispecies waste water biofilms when it was combined with silver nitrate [60,61]. To account for the enhanced inhibition observed when the flavonoids were loaded in the nanocapsules, we can argue that there is a local delivery effect, that it is enhanced at low concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Yet another possible target could be the phytochemicals compounds able to enhance dispersal of biofilms mainly by targeting the breakdown of the extracellular polysaccharide that makes up the extracellular matrix. Some compounds like norspermidine have been reported to have an enhanced dispersal of multispecies waste water biofilms when it was combined with silver nitrate [60,61]. To account for the enhanced inhibition observed when the flavonoids were loaded in the nanocapsules, we can argue that there is a local delivery effect, that it is enhanced at low concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Another possible target site for antibiofilm activity is dispersal of biofilms mainly by targeting the breakdown of the extracellular polysaccharide that makes up the extracellular matrix. Phytochemical compounds like norspermidine have been found to possess this property [ 46 ]. Therefore, at it could be concluded that the test extracts did not possess any of these activities and therefore could not be good candidates for management of biofilms related to this test isolate.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, several genes associated with the release of exDNA or with autolysis as well as quorum sensing inhibitors can be the target of an anti-biofilm therapy (e.g. Bao et al 2015; Beltrame et al 2015; Si et al 2015; reviewed by Wolska et al 2016). A nanomaterial cleaving exDNA of S. aureus biofilms was also proposed as a promising therapeutic material against biofilms (Thiyagarajan et al 2016).…”
Section: Applicationsmentioning
confidence: 99%